Improving the sustainability of the urban environment in the Bashgah Naft neighborhood of the 21st district of Tehran (with emphasis on the smart growth approach) - Lotfali Kozegar Kaleji; Parviz Aghaei; Sajad Saeedi (علوم محیطی)
Introduction: One of the most important and complex social developments in the world in the last half century is the development of urbanization. Due to scattered growth in many cities in the world, natural resources are not used properly. The increase in environmental concerns, economic and social inequalities as a result of the expansion of urban spaces, caused attention to new urban design and planning strategies, including the smart urban growth strategy. In fact, the smart growth strategy is one of the most acceptable approaches to face such a situation, which, while preserving the environment, meets the needs of today's urban society.Material and methods: The current research is of a practical and practical type, the purpose of which is to overlap the environmental indicators of the Bashgah Naft neighborhood, with an emphasis on the smart growth approach, with a descriptive-analytical method, and in order to evaluate the indicators and the state of the situation, a survey method was used to measure opinions and Thoughts go on. The process of collecting research information is a review of library texts and the most used sources are specialized books and magazines and the use of the global information network. The studied space of Bashgah Naft neighborhood is from district 21 of Tehran city, according to the last census of 2015, the population of the neighborhood is 60,163 people, sampling is based on random method and using Cochran's formula with an error rate of 5%, the statistical sample is 381 people. Independent sample t-tests are used in data analysis.Results and discussion: According to the presented theoretical foundations and also after examining the indicators of urban environment and indicators of smart urban growth and examining the background of their researches, the indicators of urban environment were overlapped with an emphasis on the approach of smart urban growth and in the form of four criteria, 12 sub-criteria and 47 Indicators were proposed and the relationship between the indicators and their sub-criteria and criteria has been determined. The indicators of the research were investigated using the t-test of one sample, and after measuring the t-test in the indicators and sub-criteria, it was determined that only four indicators out of 47 indicators and two sub-criteria out of 12 sub-criteria are average. Regarding 44 indicators and 10 other sub-criteria, according to their significance level, in some of them, due to the positive difference of the mean and the numbers of the upper and lower limits obtained, it indicates the intensity in that index or sub-criteria, and in the rest of them, according to The negativity of the average difference and the numbers of the upper and lower limits obtained indicates weakness in that index or subcriterion.Conclusion: According to the assumption of the research that the Bashgah Naft neighborhood is moderately compatible with the overlapped indicators of the urban environment with an emphasis on the smart growth approach; After conducting the desired test and analyzes, it can be concluded that the level of compatibility of  Bashgah Naft neighborhood with the overlapped indicators is not up to the average level.